2019
DOI: 10.1371/journal.pone.0215848
|View full text |Cite
|
Sign up to set email alerts
|

Integrating across memory episodes: Developmental trends

Abstract: Memory enables us to use information from our past experiences to guide new behaviours, calling for the need to integrate or form inference across multiple distinct episodic experiences. Here, we compared children (aged 9–10 years), adolescents (aged 12–13 years), and young adults (aged 19–25 years) on their ability to form integration across overlapping associations in memory. Participants first encoded a set of overlapping, direct AB- and BC-associations (object-face and face-object pairs) as well as non-ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 26 publications
7
36
0
Order By: Relevance
“…Memory integration has been examined in nonhuman animals (e.g., Bunsey & Eichenbaum, 1996; DeVito, Lykken, Kanter, & Eichenbaum, 2010) and in both human adults and developing children (e.g., Bauer & San Souci, 2010; Preston, Shrager, Dudukovic, & Gabrieli, 2004; respectively). It has been approached using behavioral assays (e.g., Bauer & Larkina, 2017; Shing et al, 2019; Varga & Bauer, 2017b), neuroimaging techniques (e.g., Sweegers, Takashima, Fernández, & Talamini, 2014; Varga & Bauer, 2017a; Zeithamova & Preston, 2010), as well as computational modeling (e.g., McClelland, McNaughton, & O’Reilly, 1995; Norman & O’Reilly, 2003). The process of memory integration has garnered such intense attention because understanding how it works provides key insights into how memory networks are organized and reorganized with experience.…”
mentioning
confidence: 99%
“…Memory integration has been examined in nonhuman animals (e.g., Bunsey & Eichenbaum, 1996; DeVito, Lykken, Kanter, & Eichenbaum, 2010) and in both human adults and developing children (e.g., Bauer & San Souci, 2010; Preston, Shrager, Dudukovic, & Gabrieli, 2004; respectively). It has been approached using behavioral assays (e.g., Bauer & Larkina, 2017; Shing et al, 2019; Varga & Bauer, 2017b), neuroimaging techniques (e.g., Sweegers, Takashima, Fernández, & Talamini, 2014; Varga & Bauer, 2017a; Zeithamova & Preston, 2010), as well as computational modeling (e.g., McClelland, McNaughton, & O’Reilly, 1995; Norman & O’Reilly, 2003). The process of memory integration has garnered such intense attention because understanding how it works provides key insights into how memory networks are organized and reorganized with experience.…”
mentioning
confidence: 99%
“…This type of representation (Brunec et al, 2018; may be supported by the late-developing (Calabro et al, 2020;Demaster et al, 2016;Gogtay et al, 2004;Langnes et al, 2020) anterior hippocampus via its connections with medial prefrontal cortex . Consistent with these past neural observations, behavioral evidence also suggests that children do not spontaneously store complex, higher-order relations that unfold across multiple experiences in memory until at least early adolescence (Bauer et al, 2012(Bauer et al, , 2020Schlichting et al, 2021;Shing et al, 2019). On the whole, existing research would therefore suggest later development of memory for meaningful groupings relative to specific associations.…”
mentioning
confidence: 66%
“…Despite their apparent contradiction with some findings, our results of an increasing tendency to extract higher-order associative structure with development are consistent with numerous other studies on memory integration. Such studies have shown developmental increases in the tendency to combine across multiple memories to generate new inferences, both when self-deriving new semantic knowledge (Bauer et al, 2012(Bauer et al, , 2020, as well as inferring novel associations between items indirectly related through a common link (Schlichting et al, 2016(Schlichting et al, , 2021Shing et al, 2019). Relevant to the present work, older more than younger learners attribute shared features to items originally experienced close in time in an exposure sequence (i.e., a member of the same "temporal community"; Pudhiyidath et al, 2020), consistent with our finding that adults and older but not younger children may link together group members in memory.…”
Section: Discussionmentioning
confidence: 99%
“…We used a musical adaption of a visual associative inference task that has previously been used to study memory integration in behavioral and fMRI studies 21,22,[25][26][27]. In the musical variant, participants learned overlapping pairs of objects and melodies (object-melody and melody-object pairs; i.e.…”
Section: Musical Associative Inference Taskmentioning
confidence: 99%
“…We compared professional musicians and non-musicians by using a visual-melodic variant of an associative inference task 21,22 , a paradigm that is frequently used to study memory integration. Participants were required to memorize overlapping melody-object pairs and to form an integrated memory of these associations.…”
Section: Introductionmentioning
confidence: 99%